TelePix2: full scale fast region of interest trigger and timing for the EUDET-style telescopes at the DESY II test beam facility - Huth, Lennart; Augustin, Heiko; Dittmann, Lucas; Dittmeier, Sebastian; Hammerich, J.; He, Y.; Herkert, A.; Immig, David; Kim, D.; Krämer, U.; Kolb, R.; Perić, I.; et al. (Nuclear instruments & methods in physics research. Section A, Accelerators, spectrometers, detectors and associated equipment, 2025)
With increasing demands by future and current upgrades of particle physics experiments on rate capabilities and time resolution, the requirements on test beams are also increasing. The current infrastructure at the DESY II test beam facility includes particle tracking telescopes with long integration times, no additional timing but excellent spatial resolution. This results in readouts with multiple particles per trigger, causing ambiguities in tracking and assigning particles to triggers. Also, it is likely not to trigger on particles that pass through a small device under test, leading to inefficient data taking. These issues can be solved by adding TelePix2 as a timing and flexible region of interest trigger layer. TelePix2 is a full scale HV-CMOS chip based on the successful small scale prototype TelePix. The DAQ system and the sensor’s performance featuring efficiencies above 99% and a time resolution of 3.844(2)ns are presented. The integration into EUDAQ2 and the AIDA-TLU to seamlessly work in the test beam environment as well as into the analysis chain is described. First successful use cases are highlighted to conclude that TelePix2 is a well-suited timing and trigger layer for test beams.
Gesehen am 12.01.2026